Review: Intrauterine growth restriction, diagnosis and physiological characterisation in pigs - R. Ruggeri; G. Bee; C. Ollagnier (Animal, 2025)
The economy of modern pig breeding programs relies largely on sow reproductive performance. Over the last decades, genetic selection in the sow breeding sector has focused on increasing the number of piglets born per litter. As a result, highly prolific sows now often give birth to 18–20 live piglets. However, in parallel with the improved prolificacy, there has been an increase in the number of piglets experiencing growth restriction during foetal development, a marked decline in the birth body weight (BtW) of the piglets, and an increase in perinatal mortality rates. Intrauterine growth restriction (IUGR) is defined as the inability of the foetus to achieve its expected growth potential during gestation. Insufficient space within the uterus represents a primary factor contributing to IUGR in highly prolific sows. Uterine overcrowding is indeed associated with reduced placental weight and decreased uterine blood flow per foetus. The impaired uteroplacental blood flow results in inadequate distribution of metabolic substrates to the foetus, which develops poorly. In this context, the supply of oxygen and nutrients to the vital organs is prioritised, leading to preserved brain development, often at the detriment of other organs like the liver and the small intestine. This adaptive mechanism, termed the “brain-sparing effect”, results in a relative increase in brain size compared to other organs. Therefore, an appropriate measure for assessing the severity of IUGR in piglets is the ratio between brain weight and the weight of other organs. However, since IUGR often results in low-BtW piglets with a distinctive head shape, the diagnosis is commonly based on the piglet BtW and/or head morphology due to their practical applicability, despite the risk of misclassification. Piglets affected by IUGR have insufficient energy reserves and display low vitality at birth. If they survive the neonatal period, they usually face higher morbidity and mortality, impaired growth, reduced nutrient efficiency, and delayed time to slaughter. The lack of an accurate diagnostic method for IUGR remains a major challenge, limiting the development of effective interventions. Given these reasons and the fact that IUGR piglets can constitute up to 30% of a litter, the impact of this condition on the pig production system is significant, leading to a decrease in overall production efficiency. This review aims to provide an updated overview of the physiological features, diagnostic challenges, and long-term consequences of IUGR in pigs, and to discuss potential approaches for improving early detection and management strategies.